Flow rate measurements in hydropower plants using the pressure-time method – Experiences and improvements. (August 2019) - Adamkowski, Adam; Janicki, Waldemar; Krzemianowski, Zbigniew; Lewandowski, Mariusz
Abstract: One of the most difficult tasks in the performance tests of hydraulic machines (turbines and pumps) is related to measuring the flow rate (discharge). Particularly, this problem concerns the large-size structures, which can be found in hydropower plants. In such cases, flow rate measurement is difficult and expensive due to the need to use special measuring devices assuring sufficiently low uncertainty level of measurement results in structures of such sizes, complex geometry, difficult access to the measurement cross-sections, etc. Only a few methods fulfilling this requirement are available under the conditions occurring in hydropower plants. One of them is the pressure-time method (known as the Gibson method) which is primary method of flow rate measurement particularly used in hydropower plants equipped with large-scale derivation. The Authors present some own experiences on flow rate measurements carried out by means of the pressure-time method gathered during tests performed in hydropower plants. Presented issues are related to instrumentation, measurement methodology and computation of the flow rate based on the recorded time course of pressure difference changes in penstocks of hydraulic machines installed in hydropower plants. Improvements in the pressure-time method developed on the basis of the aforementioned experiments allow to extend the applicability of the method, e.g. to measure flow in pump mode of hydraulic machines and reduce the uncertainty of flow measurement by applying elastic waterhammer theory based approach or CFD analysis in pipelines with complex geometry. Highlights: The upper limit of integration in the calculation procedure of the pressure-time method; Measuring leaks through the closed wicket gates of turbines and accounting for the pipeline curvature in case of using the pressure-time method; Using the pressure-time method in hydraulic pump operation conditions; Using internal measuring system and analyzing the influence of dynamic properties of measuring system for the pressure-time method; A novel approach to the calculation procedure of the pressure-time method based on elastic waterhammer theory;